The beat,Heartbeat of the rain - Masheane, Napo (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2016)
My play script is a docu-drama inspired by the 1950s Drum journalists: Can Themba, Bloke Modisane, Nat Nakasa, Henry Nxumalo, Lewis Nkosi, Peter Magubane, Casey Motsitsi and Todd Matshikiza. The setting is a Sophiatown shebeen through which the characters move in and out. The central dramatic exploration hinges on female characters' experiences rather than the perspectives of the male journalists connected to them. I dramatise documented events such as Modisane's wife leaving him and taking their daughter with her, or a woman who buried her lover's body after he was beaten and stabbed to death. There are other twists and turns based on the Drum journalists writings. I play with the seriousness of politics, love affairs, and the comedy of their daily lives. My influences come from plays such as Nongogo (1959) and Sophiatown (1986). The Beat is dedicated to all the women who have been silenced and as a result became products of their consequences. Their voices remind me as a theatre maker that my poems and plays might arrive in me as pure SONGS (Dipina) or a CRY (Kodiyamalla). Sometimes their inspiration will spring from my traditional family rituals, as a PRAISE song/s (Dithoko/ Thoko), or from a simple memory of a childhood church song, a HYMN (Difela/ Sefela). At times these words will present themselves as a source of where one comes from, CLAN NAMES (Seboko/ Poko). These stories will find me in the dusty streets of my village and township HERSTORY"¦ they will touch, move, provoke, push and force me to vomit on page words that are subjects of that which we are even when silence seems inevitable.,My poetry collection fuses Sesotho and English, often within the same poem, as a way of showing how I live within and between two cultures. I write to celebrate these two tongues without compromising either language and allow each poem, to express its own musical component, tone, rhythm, and pace as it moves between stage and page. My poems converse about difficult subjects from a feminine voice. They look at family structures and dynamics, using everyday household things as metaphors. They take on deep family narratives of generational curses, births, deaths and love. There are also some more political poems about community outrage, the exploitation caused by outmoded culture and tradition, and about the nightmare that constantly wants to come out of the township.
Keywords: Uncatalogued